2011
DOI: 10.1183/09031936.00191810
|View full text |Cite
|
Sign up to set email alerts
|

Blinded 12-week comparison of once-daily indacaterol and tiotropium in COPD

Abstract: on behalf of the INTENSITY study investigators ABSTRACT: Two, once daily (q.d.) inhaled bronchodilators are available for the treatment of chronic obstructive pulmonary disease (COPD): the b 2 -agonist indacaterol and the anticholinergic tiotropium. This blinded study compared the efficacy of these two agents and assessed their safety and tolerability.Patients with moderate-to-severe COPD were randomised to treatment with indacaterol 150 mg q.d. (n5797) or tiotropium 18 mg q.d. (n5801) for 12 weeks.After 12 we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
97
1
7

Year Published

2011
2011
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 130 publications
(109 citation statements)
references
References 25 publications
4
97
1
7
Order By: Relevance
“…12 A blinded 12-week study in 1,598 patients comparing indacaterol 150 µg with tiotropium, in which treatment assignment was blinded, found that although the two treatments had closely similar bronchodilator effects (on trough FEV 1), indacaterol had a statistically significantly better effect on breathlessness (TDI scores), use of as-needed salbutamol, and health status (SGRQ scores). 42 On the other hand, tiotropium has established efficacy in reducing COPD exacerbations, 38,39 while the efficacy of indacaterol in this respect has not yet been fully investigated.…”
Section: Place Of Indacaterol In Treatment Algorithmmentioning
confidence: 99%
“…12 A blinded 12-week study in 1,598 patients comparing indacaterol 150 µg with tiotropium, in which treatment assignment was blinded, found that although the two treatments had closely similar bronchodilator effects (on trough FEV 1), indacaterol had a statistically significantly better effect on breathlessness (TDI scores), use of as-needed salbutamol, and health status (SGRQ scores). 42 On the other hand, tiotropium has established efficacy in reducing COPD exacerbations, 38,39 while the efficacy of indacaterol in this respect has not yet been fully investigated.…”
Section: Place Of Indacaterol In Treatment Algorithmmentioning
confidence: 99%
“…QVA149 is a novel, inhaled, once-daily dual bronchodilator combining a fixed-dose of the LABA indacaterol and the LAMA glycopyrronium (NVA237), in development as a maintenance treatment for COPD. Both components of QVA149 are approved as single agents for the treatment of moderate-to-severe COPD, and their efficacy and safety has been demonstrated in large, randomised phase III studies [12][13][14][15][16][17][18][19]. Pivotal phase III studies have recently demonstrated the efficacy and safety profiles of once-daily QVA149 in patients with moderate-to-very severe COPD [20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…Kategori A'da yer alan stabil KOAH hastalarına farmakolojik tedavi olarak ilk tercih edilecek ilaçlar gerektiği durumda kısa etkili bronkodilatörlerdir (kısa etkili (8,10). Bu iki uzun etkili bronkodilatör ilacın plaseboyla karşılaştırıldığı INHANCE çalışmasında 12. haftada trough FEV 1 değerinde indakaterol kolunda 180 mL, tiotropium kolunda 140 mL, artışla plaseboyla karşılaştırıldığın-da anlamlı iyileşme saptandı (11).…”
Section: Introductionunclassified